A Contrastive Rhetoric of Algerian Students’ Use of Connectivity - HAMADOUCHE, Mokhtar (Journal of Human Sciences, 2014)
As every speech community may have unique codes for oral communication, it may also have some culture-specific rhetorical patterns and organizational modes in terms of written language. Accordingly; when relying on their first language writing conventions to write in the target language, foreign language learners will face difficulties in conforming to the latter’s stylistic standards, regardless to their grammatical and lexical proficiency. The present paper provides a contrastive rhetoric investigation of Algerian university students’ use of connectivity across their Arabic and English writing to see whether they reach a rhetorical style closer to that of the target language, or they keep relying on their Arabic rhetorical strategies to write in English. Results revealed that students used the targeted features in a similar pattern in the two languages, and this clearly demonstrates the role of the first language in students’ target language writing.